2017
DOI: 10.1002/pat.4080
|View full text |Cite
|
Sign up to set email alerts
|

A parametric investigation of the friction performance of PC‐ABS parts processed by FDM additive manufacturing process

Abstract: The friction performance is an important factor of parts processed by fused deposition modeling (FDM) for various engineering applications. It is one type of failure made of surface contact. The proper use of FDM process parameters can bring a significant reduction in friction and the amount of wear, thereby leading to a reduction in the material waste. To date, very little studies have been performed in this area. This paper investigates the effect of FDM manufacturing parameters on the friction performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Among all the 3D‐printing technologies, fused deposition modeling (FDM) is the most widely used method due to its simplicity to operate and low cost, which attracts much attention both from industry and academia 2,3 . At present, the researches on FDM technology mainly focus on improvement of printing equipment, optimization of printing parameters, development of printing material and application, among which material development is an important research direction 1,4‐6 . The feedstock material for FDM is required with suitable processability and good dimensional stability, such as acrylonitrile‐butadiene‐styrene (ABS) and poly(lactic acid) (PLA) 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Among all the 3D‐printing technologies, fused deposition modeling (FDM) is the most widely used method due to its simplicity to operate and low cost, which attracts much attention both from industry and academia 2,3 . At present, the researches on FDM technology mainly focus on improvement of printing equipment, optimization of printing parameters, development of printing material and application, among which material development is an important research direction 1,4‐6 . The feedstock material for FDM is required with suitable processability and good dimensional stability, such as acrylonitrile‐butadiene‐styrene (ABS) and poly(lactic acid) (PLA) 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…22 In FDM/FFF, the analysis of friction, as a function of the process parameters, is particularly important for the application of the technique in various engineering elements. 23 One way to describe the friction force or estimate the magnitude of the resistance of the relative movement between bodies, is through the coefficient of friction (COF), which can be static (ls) or dynamic (ld). 19,24,25 Some researches showed that the friction coefficient of the printed parts varies according to parameters such as: building orientation, layer thickness, raster angle, air gap, and infill density.…”
Section: Introductionmentioning
confidence: 99%
“…19,24,25 Some researches showed that the friction coefficient of the printed parts varies according to parameters such as: building orientation, layer thickness, raster angle, air gap, and infill density. 23,[26][27][28] The adjustment of the printing variables has an impact on the improvement of the characteristics of the parts, such as the smoothing of the surfaces-that is, reducing the roughness and the magnitude of the staircase effect 23 -and minimizing the porosity, 28 which generates a decrease in the COF. In addition, the parametric configuration can induce, in some materials, such as poly(lactic acid) (PLA) and high temperature PLA (HT-PLA), the occurrence of the stick-slip phenomenon, thus generating greater divergences between the friction coefficient static and dynamic components produced.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most popular AM technologies, fused deposition modeling (FDM) is widely used for polymer printing . FDM typically fabricates parts using environment‐friendly thermoplastic materials like polylactic acid (PLA), polyglycolic acid (PGA), acrylonitrile butadiene styrene (ABS), and nylon, which are melted in the form of filaments and stacked layer by layer to fabricate parts …”
Section: Introductionmentioning
confidence: 99%